Pharmacists as Interprofessional Collaborators and Leaders through Clinical Pathways - Sherine Ismail; Mohamed Osman; Rayf Abulezz; Hani Alhamdan; K. H. Mujtaba Quadri (MDPI AG, 2018)
Pharmacists possess pivotal competencies and expertise in developing clinical pathways (CPs). We present a tertiary care facility experience of pharmacists vis-a-vis interprofessional collaboration for designing and implementing CPs. We participated in the development of CPs as leading members of a collaborative team of healthcare professionals. We reviewed literature, aligning it with hospital formulary and institutional standards, and participated in weekly team meetings for six months. Several tools and services were adapted to guide prescribing and standardization of care through time-bound order sets. Fifteen CPs leading to admissions in medical wards were developed and integrated into Computerized Prescriber Order Entry (CPOE) sets. Tools and services included (1) reporting of creatinine clearance to guide optimum dosing; (2) advisory flags for dosing and infusion rates; (3) piloting of medication reconciliation and counseling services before discharge were initiated; (4) Arabic drug leaflets were designed to educate patients; and (5) five CPs were included in pragmatic randomized control trials with a clinical pharmacist as co-investigator. Clinical pharmacists conducted continuous orientation to various healthcare professionals throughout the process. CPs provide unique opportunities for establishing and evaluating patient-centered pharmaceutical services and allow clinical pharmacists to demonstrate interprofessional leadership in collaboration with multidisciplinary teams.